THE RISK BEHAVIOUR OF HIV/AIDS TRANSMISSION IN THE LGBT GROUP IN MADIUN - ratnawati, riska (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2018)
Incidence of human immonudeficiency virus (HIV) acquired immune deficiency syndrome (AIDS) has been increasing for the last ten years in indonesia, including madiun.